2018
DOI: 10.1186/s12870-018-1426-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide contributes to methane-induced osmotic stress tolerance in mung bean

Abstract: BackgroundOsmotic stress is a major abiotic stress limiting crop production by affecting plant growth and development. Although previous reports discovered that methane (CH4) has a beneficial effect on osmotic stress, the corresponding downstream signal(s) is still elusive.ResultsPolyethylene glycol (PEG) treatment progressively stimulated the production of CH4 in germinating mung bean seeds. Exogenous CH4 and sodium nitroprusside (SNP) not only triggered nitric oxide (NO) production in PEG-stressed plants, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…2-(4-Carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt (cPTIO) was regarded as a scavenger of NO [51][52][53][54]. Tungstate (Tg; an inhibitor of NR [28,33,37,[55][56][57];) and N G -nitro-L-arginine methyl ester hydrochloride (NAME; an inhibitor of mammalian NOS-like enzyme [25,33,[36][37][38][39];) were also applied. In this study, the concentrations of above chemicals were determined in the pilot experiments, from which the significant responses were observed.…”
Section: Chemicalsmentioning
confidence: 99%
“…2-(4-Carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt (cPTIO) was regarded as a scavenger of NO [51][52][53][54]. Tungstate (Tg; an inhibitor of NR [28,33,37,[55][56][57];) and N G -nitro-L-arginine methyl ester hydrochloride (NAME; an inhibitor of mammalian NOS-like enzyme [25,33,[36][37][38][39];) were also applied. In this study, the concentrations of above chemicals were determined in the pilot experiments, from which the significant responses were observed.…”
Section: Chemicalsmentioning
confidence: 99%
“…Under osmotic stress, not only did the sugar content in maize root tissues increase by CH 4 (exogenously applied 0.65 mM), but the sugar and AsA metabolism in maize seedlings were also regulated by CH 4 [66]. Further research found a positive role of endogenous NO in CH 4 -enhanced plant tolerance against osmotic stress in mung beans [46]. This research also suggested that NO-regulated redox homeostasis and S-nitrosylation might take part in the above CH 4 action (Table 5).…”
Section: Plant Species Abiotic Stress and Its Effect Ch 4 Roles Undermentioning
confidence: 88%
“…Liao et al [45] found that marigold explants also stimulated NO production under drought stress. Exogenous CH 4 and sodium nitroprusside triggered the production of NO under osmotic stress [46]. Recently, studies have found that heavy metal aluminum stress induced NO generation in wheat [5,47] and peanut [48].…”
Section: Nitric Oxide (No)mentioning
confidence: 98%
See 2 more Smart Citations